Surface modification by superimposing piecewise shape function satisfying hull variation given by arbitrary characteristic curve on surface. Issue 4 (7th July 2021) - Luong, Quang-Phap; Nam, Jong-Ho
Abstract: The ship hull form is directly related to each design phase of a ship. This form is thus frequently designed based on a variation of a well-made parent ship to avoid new design risks. However, in hull form variation, satisfactory geometric preservation and good performance continuity of the parent ship are considered competing requirements. To effectively facilitate the variation, an appropriate compromise between these requirements should be achieved. Instead of altering hull form parameters, we propose a flexible and intuitive approach to interactively vary the hull surfaces with arbitrary curve constraints and to focus on preserving the properties of the original hull surface. The advantage of the superposition of the curve or surface is leveraged to modify the hull shape. An intermediate surface that satisfies an intermediate curve constraint and has a smooth shape is constructed and superimposed on the top of the original surface to yield the desired surface. A shape control mechanism using a shape function simplifies the control of the surface modification with a curve constraint. The developed method was applied to modify the characteristic curves and section curves situated on the stern part of a container vessel. The changes in the geometric shape and hydrodynamic performance due to the curve-constraint variation were assessed to demonstrate the practicality and efficiency of the proposed method. The results show that the proposed method produces a smooth shape and almost unchanging hydrodynamic patterns. The proposed variation provides an effective tool for varying the hull in a linear fashion. Graphical Abstract: